2017
DOI: 10.1002/slct.201601542
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids‐Based Iron Phosphide/Carbon Nanotubes Composites: High Active Electrocatalysts towards Hydrogen Evolution Reaction

Abstract: New catalyst for hydrogen generation by water electrolysis in aqueous acid is made by mixing N,N‐bis(4‐ (methoxycarbonyl)benzyl)‐N‐methyl‐d‐glucaminium bromide (MBMG−Br) and trichloroferrate (III) to form the iron containing ionic liquid (IL), MBMG‐FeCl3Br. This IL is mixed with carbon nanotubes (CNTs) and sodium hypophosphite (NaH2PO2) and then heated to 300 oC in an inert atmosphere to give the final catalyst, a CNT‐supported iron phosphide (FePMBMG/CNT), which exhibits catalytic activity toward hydrogen evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…ILs containing transition metal anions (such as FeCl 4 − , NiCl 3 − , and CoCl 3 − ) have been extensively studied [ 101 , 102 , 103 , 104 ]. This kind of ILs has the ability to provide metal elements for catalytic materials for water splitting [ 105 , 106 ]. A more ingenious design is to use metal anions and quaternary phosphonium salt cations to form ILs, such as [P 66614 ] 2 CoCl 4 [ 98 , 99 ], [P(C 6 H 13 ) 3 C 14 H 29 ]FeCl 4 [ 107 ], among others.…”
Section: Ionic Liquids As Reactive Reagents For Electrocatalysts Of H...mentioning
confidence: 99%
See 1 more Smart Citation
“…ILs containing transition metal anions (such as FeCl 4 − , NiCl 3 − , and CoCl 3 − ) have been extensively studied [ 101 , 102 , 103 , 104 ]. This kind of ILs has the ability to provide metal elements for catalytic materials for water splitting [ 105 , 106 ]. A more ingenious design is to use metal anions and quaternary phosphonium salt cations to form ILs, such as [P 66614 ] 2 CoCl 4 [ 98 , 99 ], [P(C 6 H 13 ) 3 C 14 H 29 ]FeCl 4 [ 107 ], among others.…”
Section: Ionic Liquids As Reactive Reagents For Electrocatalysts Of H...mentioning
confidence: 99%
“…Fe 2 P/CNT exhibited excellent HER performance with current densities of 10 and 20 mA cm −2 at overpotentials of 115 and 150 mV, respectively. FeP(MBMG)/CNT, stemmed from [MBMG]FeCl 3 Br with CNTs and NaH 2 PO 2 [ 105 ], exhibited high activity for water splitting. This strategy can make not only the phosphorus and metal elements arrange according to the IL-induced structure but also evenly distribute and have many active sites.…”
Section: Ionic Liquids As Reactive Reagents For Electrocatalysts Of H...mentioning
confidence: 99%
“…56–58 It is found that these ionic liquids could provide a kind of ion source for synthesis of catalytic materials for hydrogen evolution, which is also different from ionic liquids generally used as precursors. In 2017, Cui et al 59 reported the reaction of ionic liquid (MBMG-FeCl 3 Br) with carbon nanotubes (CNTs) and sodium hypophosphate (NaH 2 PO 2 ) to obtain CNT-supported iron phosphating (FeP MBMG /CNT) catalyst. It was found by comparative experiments that FeP (MBMG) /CNTs exhibited high activity among all synthesized catalysts.…”
Section: Ionic Liquids and Their Functions In Electrocatalytic Hydrog...mentioning
confidence: 99%
“…In acidic conditions, FeP/CNT samples (typical SMNCs) synthesized via IL-assistance were the first to be employed as electrocatalysts for exploring their HER activity (Table 2) [156]. As the Fe atoms were highly dispersed in IL molecules, the produced metal NPs featured a small size and a good dispersion, which ensures an abundance of accessible active sites.…”
Section: Application Of Smncs In the Electrochemical Hermentioning
confidence: 99%